If it's not what You are looking for type in the equation solver your own equation and let us solve it.
11=q/10+8
We move all terms to the left:
11-(q/10+8)=0
We get rid of parentheses
-q/10-8+11=0
We multiply all the terms by the denominator
-q-8*10+11*10=0
We add all the numbers together, and all the variables
-1q+30=0
We move all terms containing q to the left, all other terms to the right
-q=-30
q=-30/-1
q=+30
| w-75=187 | | x=-4/2(1/3) | | 5x+2(x-3)=8x+2 | | 22x+35=0 | | -9y-5=13 | | s/9+56=61 | | 187=75-w | | n/6+4=2 | | -50+-s=-25 | | 7y=6-20 | | 10(z-92)=40 | | y=1/3(6)^2+4(6)-15 | | 3(q-7)=69-6 | | 45=6y;y= | | 14=x+5-6x | | 5/12x5/12=0.65x9= | | 48+90+y=180 | | −x2+6x+7=0 | | p-68/8=3 | | 4x^2-5x+3=2 | | 5/12x5/12=0.65 | | a-64.9=4 | | -5+3c=8c | | 5+7a=19a= | | 3x+3+2x=164 | | -8w+38=-50 | | x/2-7=9 | | 8t-20=6t+12 | | 2b÷3+1=2b | | -10+7t=6t | | 70=-5x+5(4-4x) | | -2x+5x-15=3(x-4)-34 |